Development of the Krakow University Oral and Maxillofacial Surgery since 1951 until today - Stypułkowska, Jadwiga; Wyszyńska-Pawelec, Grażyna; Zaleska, Małgorzata; Zapała, Jan; Panaś, Maria; Kurek, Marian; Szuta, Mariusz; Kaczmarzyk, Tomasz (Journal of Stomatology, 2015)
The article presents evolution of Krakow University of oral and maxillofacial surgery, initially at Krakow’s Medical Academy (1951-1993), and subsequently at the Medical College of the Jagiellonian University. It also contains portraits of successive heads of departments who – together with their co-workers – developed didactic, scientific and therapeutic activity in the field of oral and maxillofacial surgery. Since reorganisation in 1996, Department of Oral Surgery has functioned upon University Dental Clinic, which allows for strict interdisciplinary didactic- scientific and diagnostic-therapeutic cooperation with other dental departments, while Deparment of Cranio- Maxillofacial Surgery has been located in the Ludwik Rydygier’s Hospital. Appropriate accomodation with modern medical equipment ensures interdisciplinary didactic-scientific and diagnostic-therapeutic cooperation of world-class quality. Finally, article presents scientific and professional achievments of both departments of oral and maxillofacial surgery (postdoctoral dissertations, PhD theses, articles, congress reports and specializations) since 1951 until today.